(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The analysis of bioactive was done by used gas chromatography-mass spectroscopy(GC-MS) method then antifungal and antimicrobial activity for methanolic extract was measured in the lab. The analysis of Morganella morganii by GC-MS revealed the existence of the Tricyclo, 3-Methoxybenzaldehyde semicarbazone , undecan-1-amine, carboxaldehyde , 1-methyl-,oxime ,(Z)-(+), 4-(2,5-Dihydro-3-methoxyphenyl) butylamine , Paromomycin , 1,5,5-Trimethyl-6-methylene-cyclohexene, 9-Borabicyclo[3.31], Benzenemethanol , nonane , 9-mercapto-2-(2-aminopropoxy)-3-methyl, Acetamide , N-(6-acetylaminobenzothiazol-2-yl)-2-(adamantan, rin-6-carboxylic acid , N-(2,5-Dicyano-3,4-dihydro-2H-pyrrol-2-yl)- acetamide, 3,10-Dioxatricyclo4-(2,5-Dihydro-3-methoxyphenyl)butylamine, [4.3.1.0(2,4)] phenylmethyl ester, 3,7-Diazabicyclo dec-7-ene, 3-Cyclohex-3-enyl-propionic acid, Eicosanoic acid [3.3.1] 9,9-dimethyl-, nonane ,Dithiocarbamate , dl-Homocysteine, 2-(2-Furyl)pyridine, S-methyl-,N-(2-methyl-3-oxobutyl)-, 1,7-Dioxa-10-thia-4,13-diazacyclopentadeca-5,9,12-trione, 5,7-Dodecadiyn-1,12-diol, 1-(β-d-Arabinofuranosyl)-4-O-difluoromethyluracil, Uric acid, Pyrrolo[1.2-a]pyrazine-1,4-dione , hexahydro-,12-Methyl-oxa-cyclododecan-2-one, Phthalic acid , butyl undecyl ester, 9,12,15-Octadecatrienoic acid , 2,3-bis(acetyloxy)propyl ester, , methyl ester, 12-Dimethylamino-10-oxododecanoic acid , 1,2,4-Trioxolane-2-octanoic acid 5-octyl-, Octahydrochromen-2-one, L-Aspartic acid, N-glycyl-,2H-Oxecin-2-one , 3,4,7,8,91,10-hexahydro-4-hydroxy-10-meth, Thiazolo[4,5-d]pyrimidine-5,7(4H,6H)-dione , 3,6,12-Trimethyl-1,4,7,10,13,16-hexaaza-cyclooctadecane, 2-lodohiistidine, 2-amino-4-(2-ph,Dec-9-en-6-oxo-1-ylamide,2,5-Piperazinedione,3,6-bis(2-ethylpropyl)-, 9-Octadecenamide , (Z)-, 3’,8,8’-Trimethoxy-3-piperidyl-2,2’-binaphthalene-1,1’,4,4’-tetra . Citrullus colocynthis (Crude) was very highly active (6.39±0.27) mm anti-fungal activity of Morganella morganii showed that unstable compounds ( volatile )were effective hight to decrease the growth of Aspergillus terreus (5.613±0.23). the production of Morganella morganii give many essential secondary metabolites with a lot of biological activities. in pharmacy we depend on the significance of using bioactive compounds to made drugs for many diseases as for treatment, compounds purification of which produced by Morganella morganii will be benefit for use.